Enhanced-Peroxidatic Activity in Specific Catalase Isozymes of Tobacco, Barley, and Maize - Havir, Evelyn A. (1989)
Separation of catalase isozymes from leaf extracts of three diverse plant species (Nicotiana sylvestris, Zea mays, Hordeum vulgare L.) revealed a distinct isozyme with enhanced peroxidatic activity (30-, 70-, 28-fold over typical catalase, respectively) which constituted 10 to 20% of the total catalase activity. In maize this isozyme is the product of the Cat3 gene, which is expressed only in mesophyll cells (AS Tsaftaris, AM Bosabalidis, JG Scandalios [1983] Proc Natl Acad Sci USA 80: 4455-4459). A mutation in barley reducing levels of peroxisomal catalase (AC Kendall et al. [1983] Planta 159: 505-511) does not reduce the amount of the isozyme with enhanced peroxidatic activity. Similarly, this isozyme is unaffected in dark-grown barley in spite of a 75% decrease in total catalase activity. These results suggest that this catalase isozyme is under separate genetic control in barley. This may also be the case in tobacco where the catalase isozyme with enhanced peroxidatic activity is an immunologically distinct protein (EA Havir, NA McHale [1989] Plant Physiol 89: 952-957).